A Review on Bacterial Cellulose: Properties, Applications, Fermentative Production, and Molasses Potential as Alternative Medium - Angela, Clara; Devanthi, Putu Virgina Partha (Indonesian Journal of Life Sciences, 2021)
Bacterial cellulose (BC) is an extracellular homopolymer produced by certain species of bacteria. It has demonstrated the potential as an alternative to plant cellulose with more appealing features such as unique nanostructure, high porosity, high crystallization index, high tensile strength, high water holding capacity, and a high degree of polymerization. These attributes facilitate BC utilization in various applications, ranging from the food industry, cosmetics, pharmaceutical, medical field, waste treatment, textile, and paper industry. Considering the advantages and wide range of applications, it is necessary to explore and improve the current industrial production to achieve a higher yield at a lower cost. This review article summarizes the BC properties and characteristics as well as its application in different fields. Furthermore, the potential of agricultural waste molasses for low-cost BC production is also discussed.